BFF : Best Friends Forever : Two Novels - Blume, Judy; Blume, Judy; Blume, Judy. (New York : Delacorte Press, 2007)
Contains two previously published novels by Judy Blume.
Just as long as we're together -- Here's to you, Rachel Robinson.
Maps on endpapers.
Keywords: Friendship -- Fiction; Problem families -- Fiction; Brothers and sisters -- Fiction; Gifted children -- Fiction; Interpersonal relations -- Fiction